Wald und Forst in Irland - Leister, Ingeborg (ERDKUNDE, 1963)
Ireland, which as late as the 12th century was an island covered by woods and whose climax vegetation would be an oak-ash mixed forest, possesses today less woodland than any other country in Europe. As in other parts of Europe, it was the Neolithic period with its sedentary peasantry which brought a turning point in the postglacial development of vegetation. Since, however, until the arrival of the Anglo-Normans (1172) Ireland did not know an arable farming civilisation, the clearing of areas for agriculture did not take place; the decline of the woodlands was rather a very slow process of degeneration. Although this process was accelerated by the Anglo Normans, the final destruction of the forest cover came only during the early modern period as a result of charcoal burning, and export of timber and timber products. Owing to a terrible robber exploitation Ireland probably had at the beginning of the 18th century even fewer trees than today. When land property became fully commercialized forestry was, in contrast to Germany, not one of the means of achieving it. Thanks to the sentiment of the British early romanticism plantations of trees, some quite extensive, though mostly of an ornamental character, were brought into being from 1740 onwards; this saved Ireland from becoming almost completely treeless. After a steady alter nation between increase and decrease of the areas under forest the statistically proved absolute low occurred in 1931. State forestry, founded in 1904-1908, then gradually began to gain impetus. It is unable to do much about the extreme dispersal of the forested parcels but the emphasis now definitely lies on establishing larger forests on mountain slopes which thus achieves an effective separation between farm land and woodland. A recently developed method of planting, the deep peat afforestation, has made it possible to accelerate very considerably the afforestation programme since the end of the second world war. It is also resulting in a change of emphasis from south-east to west Ireland. However, when the Irish Republic has reached its long term target, the reafforestation of 1 million acres, it will only have a forested area of 5.9% of its surface and will continue to occupy in this respect the last place amongst the states of Europe. Nevertheless the importance of forestry in the national economy has already begun to make itself felt.